Immunotoxicity Considerations for Next Generation Cancer Nanomedicines - Lysaght, Joanne; Prina Mello, Adriele (My University, 2019)
Although interest and funding in nanotechnology for oncological applications is thriving, translating these novel therapeutics through the earliest stages of preclinical assessment remains challenging. Upon intravenous administra-tion, nanomaterials interact with constituents of the blood inducing a wide range of associated immunotoxic effects. The literature on the immunological interactions of nanomaterials is vast and complicated. A small change in a particular characteristic of a nanomaterial (e.g., size, shape, or charge) can have a significant effect on its immunological profile in vivo, and poor selection of specific assays for establishing these undesirable effects can overlook this issue until the latest stages of preclinical assessment. This work describes the current literature on unintentional immunological effects associated with promising cancer nanomaterials (liposomes, dendrimers, mesoporous silica, iron oxide, gold, and quantum dots) and puts focus on what is missing in current preclinical evaluations. Opportunities for avoiding or limiting immunotoxicity through efficient preclinical assessment are discussed, with an emphasis placed on current regulatory views and requirements. Careful consideration of these issues will ensure a more efficient preclinical assessment of cancer nanomedicines, enabling a smoother clinical translation with less failures in the future
PUBLISHED
Keywords: immunological interactions of nanomaterials; immunological interactions of nanomaterials